Trends and Real-World Safety of Patients Undergoing Percutaneous Coronary Intervention for Symptomatic Stable Ischaemic Heart Disease in Australia - Hamilton, G.W.; Yeoh, J.; Dinh, D.; Reid, Christopher; Yudi, M.B.; Freeman, M.; Brennan, A.; Stub, D.; Oqueli, E.; Sebastian, M.; Duffy, S.J.; Horrigan, M.; et al. (2022)
Background: Percutaneous coronary intervention (PCI) in stable ischaemic heart disease (SIHD) has not been shown to improve prognosis but can alleviate symptoms and improve quality of life. Appropriately selected patients with symptoms refractory to medical therapy therefore stand to benefit, provided safety is proven. Methods: Consecutive patients undergoing PCI for SIHD between 2005–2018 in a prospective registry were included. Yearly comparisons evaluated trends, and a sub-analysis was performed comparing proximal left anterior descending artery (prox-LAD) to other-than-proximal LAD (non-pLAD) PCI. Outcomes included peri-procedural characteristics, in-hospital and 30-day event rates including MACE, and 5-year National Death Index (NDI) linked mortality. Results: There were 9,421 procedures included. Over time, patients were increasingly co-morbid and had higher rates of AHA/ACC class B2/C lesions, ostial stenoses, bifurcation lesions, and chronic total occlusions (all p-for-trend ≤0.001). Over 14 years, major bleeding reduced (1.05% in 2005/06 vs 0.29% in 2017/18, p-for-trend <0.001), while other in-hospital and 30-day event rates were stably low. There were only seven (0.07%) in hospital deaths and 5-year mortality was 10.3%. No differences were found in outcomes between patients who underwent prox-LAD compared to non-pLAD PCI. Major independent predictors of NDI linked all-cause mortality included an eGFR <30 mL/min/1.73 m2 (HR 4.06, 95% CI 3.26–5.06), chronic obstructive pulmonary disease (COPD) (HR 2.25, 95% CI 1.89–2.67) and LVEF <30% (HR 2.13, 95% CI 1.57–2.89). Conclusions: Although patient and procedural complexity increased over time, a high degree of procedural success and safety was maintained, including in those undergoing prox-LAD PCI. These real-world data can enhance shared decision making discussions regarding whether PCI should be pursued in patients with symptomatic SIHD refractory to medical therapy.